Is buying behavior influenced by segmentation? - Tita Hariyanti; Harun Al Rasyid; Anisa Ramadhani Kusumastiti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
Buying behavior in choosing health care is a long process. Segmentation is one of the things that underlies the decision of the patient. This study aims to determine the buying behavior of patients who do the first child labor and its relationship with buying behavior in RSIA Puri Bunda (PB) Malang. This research uses the cross-sectional method. The sampling technique used the total sampling method, ie all inpatients who gave birth to the first child at the time of this study were executed. The number of samples was 55 respondents in April-May 2017. Data were analyzed using multinomial logistic regression. The results showed that customer segmentation of RSIA PB was from Blimbing sub-district, 21-25 years old, last high school education, income <Rp.1.500.000,00, housewife, Islam, class of 3rd class and payment method using BPJS . Buying behavior of respondents is included in complex type and dissonance reducing buying behavior. Geographic, demographic, psychographic and behavioral segmentation is not related to buying behavior. Segments that have been detected are expected to get attention from the hospital to determine the marketing efforts that will be done next. In its marketing efforts, RSIA PB should pay more attention to customers who have a high-involvement type in order to provide all the information expected by the customer.